Depletion of nucleus accumbens dopamine leads to impaired reward and aversion processing in mice: Relevance to motivation pathologies. (October 2016) - Bergamini, Giorgio; Sigrist, Hannes; Ferger, Boris; Singewald, Nicolas; Seifritz, Erich; Pryce, Christopher R.
Abstract: Dopamine (DA) neurotransmission, particularly the ventral tegmental area-nucleus accumbens (VTA-NAcc) projection, underlies reward and aversion processing, and deficient DA function could underlie motivational impairments in psychiatric disorders. 6-hydroxydopamine (6-OHDA) injection is an established method for chronic DA depletion, principally applied in rat to study NAcc DA regulation of reward motivation. Given the increasing focus on studying environmental and genetic regulation of DA function in mouse models, it is important to establish the effects of 6-OHDA DA depletion in mice, in terms of reward and aversion processing. This mouse study investigated effects of 6-OHDA-induced NAcc DA depletion using the operant behavioural test battery of progressive ratio schedule (PRS), learned non-reward (LNR), learned helplessness (LH), treadmill, and in addition Pavlovian fear conditioning. 6-OHDA NAcc DA depletion, confirmed by ex vivo HPLC-ED, reduced operant responding: for gustatory reward under effortful conditions in the PRS test; to a stimulus recently associated with gustatory non-reward in the LNR test; to escape footshock recently experienced as uncontrollable in the LH test; and to avoid footshock by physical effort in the treadmill test. Evidence for specificity of effects to NAcc DA was provided by lack of effect of medial prefrontal cortex DA depletion in the LNR and LH tests. These findings add significantly to the evidence that NAcc DA is a major regulator of behavioural responding, particularly at the motivational level, to both reward and aversion. They demonstrate the suitability of mouse models for translational study of causation and reversal of pathophysiological DA function underlying motivation psychopathologies. Highlights: 6-OHDA reliably decreased tissue-level dopamine (DA) in nucleus accumbens (NAcc) of mice. Decreased NAcc DA impaired reward motivation under effortful operant conditions. Decreased NAcc DA impaired motivation to control aversion under effortful conditions. Mouse models can be applied to study dopamine pathophysiology in amotivation.